AL-SHIRA’ AL-SIYAASIY FI RIWAAYAT AL-KARNAK LI NAJIB MAHFUZ WIFQA NADHARIYYAT RALF DAHRENDORF - Zaimatil Ashfiya; Faris Maturedy; Nafisatin Najwa (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2022)
This study aims to describe the phenomenon of politic conflict experienced by the characters in the novel al Karnak by Najib Mahfudz. Therefore, the researcher uses Ralf Dahrendorf's theory of political conflict to identify social conflicts in the novel. This study uses a qualitative method with a literature study model. Then the researcher used reading and note-taking techniques to obtain data related to social conflict in al Karnak's novel. Reading technique aims to identify politic conflict events in al Karnak's novel. While the note-taking technique aims to facilitate researchers in the process of coding for each event. After the data was obtained, data analysis was carried out using the Miles, Hubarman and Saldana model. Namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that each character in the novel al Karnak wishes for a revolution in Egypt. This means that there is a strong desire to change the ideology of the state. The government, on the other hand, rejected the revolution. According to Ralf Dahrendorf's conflict theory, the government is the dominant group, while society is the dominant group. So that the government group has authority over the people